Prevalence of HIV infection and uptake of HIV/AIDs services among fishermen on the shores of Lake Victoria in Kagera region, Northwestern Tanzania. - Patrick Mwanahapa; Mtoro J Mtoro; Dina Gerald; Pius Horumpende; Salaam Mujeeb (PLoS ONE)
Introduction The Tanzania HIV Impact Survey (THIS) 2022-2023 showed that HIV prevalence among the general population stabilises but varies geographically across the country. Despite this, disproportionate burdens of HIV continue among specific subpopulations, such as fishermen. Fishermen are particularly vulnerable to HIV infection and have a low uptake of HIV prevention and treatment services. This study aimed to understand the prevalence of HIV infection, uptake of HIV/AIDs services, and associated risk factors of HIV Infection among fishermen residing along the shores of Lake Victoria in the Kagera region, Tanzania, in 2024. Methods A cross-sectional study among fishermen was employed from February to April 2024, using convenient sampling of 10 beach management units (BMUs) to obtain a robust sample of fishermen aged ≥15 years in Kagera. Participants were randomly selected across BMUs. Information was collected using an interviewer-administered questionnaire, and HIV testing was offered on-site according to national testing guidelines. Multivariable logistic regression was used to determine factors associated with HIV infection, adjusted for potential confounders. Results A total of 774 fishermen with a median age of 31 years (interquartile range: 25-38 years) were recruited. The study found an HIV prevalence of 11.3% (95% CI: 9.2-13.8). HIV prevalence varied across selected districts: 12.7% in Muleba District, 10.1% in Bukoba Rural District, and 8.6% in Bukoba Urban District. The HIV prevalence was highest among fishermen aged 20-24 years (14.7% (95% CI: 9.7-21.5). The majority, 60.9% (95% CI: 57.4-64.2), had tested for HIV in the past 12 months. Of those living with HIV, 77.6% (95% CI: 67.3-85.9) self-reported using anti-retroviral therapy. In adjusted analysis, using alcohol before sex (aOR = 2.32, 95 CI: 1.42-3.80), not testing for HIV in the last 12 months (aOR = 4.69, 95% CI: 2.79-7.88), and not using condoms (aOR = 1.94, 95% CI: 1.13-3.27) were significantly associated with HIV infection among fishermen. Conclusion HIV prevalence among fishermen was nearly twice as high as in the general population in Kagera. HIV programming should be strengthened to reduce new HIV infections. Hotspot mapping to expand HIV prevention and treatment services is pivotal for controlling the HIV epidemic.